Development of a prediction model of environmentally-sustainable behaviour among pre-service teachers in the Malaysian institute of teacher education - Abdul Karim, Aini Arifah (2021)
The inclusion of ESD in pre-service teacher education programmes is crucial in terms of preparing today's teachers for long-term success since teacher education is a critical component of ESD policy adoption and implementation. More importantly, little is known about the factors that determine the environmentally sustainable behaviour among the pre-service teachers, specifically in Malaysia Institute of Teacher Education (ITE). All the 27 campus of ITE in Malaysia are branded as 'Sustainable ITE' adopting the Eco-Schools programme which aspires to empower pre-service teachers to take action to find solutions to environmental issue in their campus area. Therefore, the main purpose of this study is to develop a preliminary predictive model on factors determining environmentally sustainable behaviour among pre-service teachers by integrating two theories; Theory of Planned Behaviour (TPB) and Model of Environmentally Responsible Behaviour (ERB). The development of the new ESB model was applied using a deductive theory-generating research approach and a correlational research design. Seven variables were examined, namely sustainability action skills (SAS), knowledge on sustainability strategies (KSS), knowledge on sustainability issues (KSI), environmentally sustainable attitude (AT), subjective norm (SN), perceived availability of facilities (PAF) and environmentally sustainable behaviour intention (BI). This study also determined the moderating role of field of study and Environment Education course on the relationship between key predictors and environmentally sustainable behaviour. PLS-SEM was applied to capture the causal effect relationship model of these relationships. The population of this study includes 5 randomly selected Institute of Teacher Education employing a stratified proportional sampling technique. The respondents (n = 256) answered the face-to-face questionnaire survey. The model's testing results revealed that out of 13 path coefficients (β) in the structural model, 8 paths had statistically significant direct effects on the interrelationships, while five path did not have any significant effect. The paths that showed significant effects were: BI, SAS, KSS, AT, SN, and PAF on environmentally sustainable behaviour; KSI and SN towards environmentally sustainable behavioural intention. The path with non-significant effects was the KSI, towards environmentally sustainable behaviour and SAS, KSI, AT and PAF towards environmentally sustainable behavioural intention. Furthermore, this study also examined the field of study and Environment Education course as moderating variables for the model. In addition to the path coefficients (direct effect relationship), the structural model also revealed 1 coefficient with significant moderating effects out of 12 for the interrelationships among the key predictors and the environmentally sustainable behaviour investigated in the study. The moderating effect was observed for Environment Education course in the relationship between knowledge on sustainability strategies (KSS) and environmentally sustainable behaviour. Overall, the structural model explained about 74.9% of the variance in the environmentally sustainable behaviour of the pre-service teachers in the ITE. In conclusion, this study verifies that environmentally sustainable behaviour intention, sustainability action skills, knowledge on sustainability strategies, attitude, subjective norm and perceived availability of facilities have a major impact on the environmentally sustainable behaviour. The study contributed significantly to the literature by indicating TPB and ERB as the ideal framework to capture the environmentally sustainable behaviour among pre-service teachers who are in their training. Additionally, this study suggests that the predictive model developed should be suitable to be used for predicting the environmentally sustainable behaviour of future teachers in the Malaysian Institutes of Teacher Education as well as other public universities and other developing countries in the hope of nurturing and cultivating positive behaviours towards mother nature, so as to achieve a more sustainable future for the next generation.